Accounting for endogenous search behavior in matching function estimation - Daniel Borowczyk Martins; Grégory Jolivet; Fabien Postel-Vinay (Institute for the Study of Labor (IZA), 2011)
We show that equilibrium matching models imply that standard estimates of the matching function elasticities are exposed to an endogeneity bias, which arises from the search behavior of agents on either side of the market. We offer an estimation method which, under certain assumptions, is immune from that bias. Application of our method to the estimation of a basic version of the matching function using aggregate U.S. data from the Job Openings and Labor Turnover Survey (JOLTS) suggests that the bias is quantitatively important.
urn:nbn:de:101:1-20110629963
Keywords: J63; J64; 330; matching function estimation; unemployment; vacancies; job finding